Sultan Muhammed [Mehmed] Hân-ı hâmis hazretleri - Altınay, Ahmed Refik, 1880?-1937. (İstanbul [İstanbul] İstanbul İstanbul [İstanbul])
6 kitap 1 ciltte (32 s., 74,4 s., 39 s., 2 s. resim, 72 s., 86 s., 166 s.)